Avaliação do grau de poluíção do solo, águas, plantas e resíduos sólidos do lixão Linha Rincão do Engenho de Lagoa Vermelha, RS - Zanchetta, Graziele Simone Boscatto (2007)
After a dump deactivation, the contamination potential may extend for several decades, being a requirement of the environmental agencies the recovery of this area. Since the urban solid wastes activity has finite period and soil has an attenuation capacity acting as a protection barrier, this recovery may be unnecessary. The research objective was to evaluate the inertization degree of solid wastes from a dump inactive for over three years and the site contamination to verify the need of recovering the area. Were characterized deposited solid wastes, soil, plants, superficial and underground waters and it was verified soil attenuations capacity regarding metals. Superficial and underground waters monitoring included physical-chemical and microbiological analyses, during the period from January to September 2006. Wastes characterization was accomplished through gravimetric composition, lixiviation and solubilization analyses, respirometry test and physical-chemical analilysis. Analyzed soil and plants inside and out of the dump, were submitted to nutrients analyses including metals to verify retention capacity and toxicity degree. Soil attenuation ability was verified in column equipment analyzing metals before and after the solution containing the analyzed metals percolation. In general, results indicated that most of disposed wastes are inert, where 80% of analyzed samples in respirometry test are stable and disposed urban solid wastes are classified as Class IIB and inert. Site soil presents high retention ability of cadmium, zinc and copper but it shows intermediary retention capacity of lead and manganese. It follows that site contamination is stagnant but there s contamination in underground waters beyond the dump by nitrates, coliforms, total dissolved solids, phosphorus, iron and manganese, besides iron, manganese, zinc and copper contamination in soil and plants